Digital Diaspora China dan Upaya Mempertahankan Eksistensi Identitas Dalam Politik Internasional [The Digital Diaspora of China and Attempts to Maintain the Existence of Identity in International Politics] - Tiara Dianti; Muhammad Yamin (Verity: Jurnal Ilmiah Hubungan Internasional (International Relations Journal), 2016)
Discussions on digital diaspora are relatively new in international relations studies. The birth of digital diaspora was driven by globalization and the increasing use of information and communications technology. The importance of digital diaspora recently has been recognized by some countries; this paper will discuss the digital diaspora of China. The emergence of digital diaspora was started by the Beijing Strategy in the Deng Xiaoping era. It has developed since the third generation of Chinese diaspora are better educated and skilled, so it is not surprising that it is easier for them to access the virtual world.Chinese Digital diaspora can be seen as a great opportunity for the country with the capacity to make use of it and include it as part of the country’s public diplomacy. The possible role of digital diaspora can be manifested through their actions in community development and political movement committed in cyberspace. Chinese Digital diaspora action is based on their strong sense of belonging to the country of origin (homeland) and a sense of nationalism.